2020
DOI: 10.1186/s13047-020-00431-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between weight‐bearing 3D bone architecture and dynamic plantar pressure measurements in the diabetic foot

Abstract: Background Measurements of plantar loading reveal foot-to-floor interaction during activity, but information on bone architecture cannot be derived. Recently, cone-beam computer tomography (CBCT) has given visual access to skeletal structures in weight-bearing. The combination of the two measures has the potential to improve clinical understanding and prevention of diabetic foot ulcers. This study explores the correlations between static 3D bone alignment and dynamic plantar loading. Methods Sixteen patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…This is the one of the few studies reporting multisegment foot kinematics on a rather large population with diabetes which were grouped by diabetes type and by the presence of DPN. In a previous effort by the present authors, several correlations were found between foot morphological parameters, such a decreased metatarsal bone distance from the floor and segments inclination, with respect to plantar-load parameters [37]. To the best of our knowledge, the effects of covariates on foot joints ROM were not accounted for in previous studies thus limiting those investigations to the analysis of populations matched by age or BMI.…”
Section: Discussionmentioning
confidence: 64%
“…This is the one of the few studies reporting multisegment foot kinematics on a rather large population with diabetes which were grouped by diabetes type and by the presence of DPN. In a previous effort by the present authors, several correlations were found between foot morphological parameters, such a decreased metatarsal bone distance from the floor and segments inclination, with respect to plantar-load parameters [37]. To the best of our knowledge, the effects of covariates on foot joints ROM were not accounted for in previous studies thus limiting those investigations to the analysis of populations matched by age or BMI.…”
Section: Discussionmentioning
confidence: 64%
“…1 ), these hardly can be introduced in routine clinical assessments, which necessarily need a quantitative response in a few minutes; rather, qualitative views of the 3D rendering of the feet can be accessible in a few seconds 31 . On the other hand, the present 3D measurements can be exploited easily in large clinical populations in case of retrospective and prospective clinical studies, as well as in complex biomechanical analyses 13 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…All these advancements may also be supported by modern visualisation modalities, for example from virtual-reality or 3D printing. The present techniques and measures shall be combined with other medical imaging 23 and biomechanical 13 , 47 , 56 , 64 analyses, for a thorough 3D radiological and functional assessments of the severity of the pathology and of the effects of treatments. Finally, distance map analyses can detect very carefully how the disruption of the skeletal structure affects the joint surface interactions under load 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model could only explain about 34% of the variance in the local peak pressure. However, the inclusion of foot architecture in the model may be of interest, especially now that innovative foot architecture measurements can be extracted from the weight-bearing CT (WBCT) [11].…”
Section: Introductionmentioning
confidence: 99%